Território, luta e educação : dimensões pulsantes nos enfrentamentos dos conflitos socioambientais mapeados no Quilombo de Mata Cavalo - Moreira, Déborah Luíza (2017)
This research grants an overview of the territory, the struggle and the education in a Quilombo’s community that for 126 years has been resisting against various violations of rights, trying to live in the place where their ancestors lived. This population has been forging resistance tactics where the struggle for schooling has been crucial to the group's existence. Assuming nature and culture as inseparable dimensions, the patrimony of nonneutral environmental education and the experiences of popular education were fertile ground for the dialogue between popular environmental education, socio-environmental conflicts, environmental justice, human and Earth´s rights. Education as a radical act has the potential to inquiry the unfair order that naturalizes inequality, and through research and the production of knowledge, we can increase the visibility of the struggles of groups marginalized by the economic system and by the colonisation´s phenomena. This radical educational act is an important step towards strengthening these groups and for building fair and democratic societies. Thus, this research proposes to map the Quilombo of Mata Cavalo (Nossa Senhora do Livramento, Mato Grosso), together with their people, the Quilombolas, the socioenvironmental conflicts experienced by the population and to understand how the local school has contributed to the strengthening of the struggle and the resistance. The quilombola complex of Mata Cavalo is formed by six communities: Aguassu, Estiva / Ourinhos, Mata Cavalo de Cima, Mata Cavalo de Baixo, Mutuca and Capim Verde. It is in the municipality of Nossa Senhora do Livramento, distant approximately 55 kilometres from the State Capital. Located in a transition area between the Cerrado (Brazilian’s savanna) and Pantanal Biomes, the quilombo has an exuberant landscape that has been altered mainly due to the expropriation of the territory by farmers, land invaders and miners. The research praxis, or methodology, was directed by the Cartography of the Imaginary and by the Social Mapping. To obtain the information that compose this investigative research, we conducted interviews, a participatory workshop about mapping of socio-environmental conflicts. The participants in these activities were residents of the community, students and teachers of the Tereza Conceição de Arruda State School. In all stages of the research, situations of environmental injustice and violations of Human and Earth Rights were denounced. The socio-environmental conflicts occur between Quilombolas and the state; Quilombolas and farmers; Quilombolas and without lands (they are not related to the Landless Workers Movement - MST); and between Quilombolas and Quilombolas. Eight are the root causes of conflicts: land dispute, real estate speculation, deforestation, cattle ranching, burning, gold mining, water dispute and pesticide use. In this plot of territorial dispute and socioenvironmental conflicts school education has become a strong tactic of struggle and resistance, which through curricular disciplines, school projects and the cultivation of fruitful bonds between school and community has been trying possible ways to strengthen the struggle for the territory and for a dignified life.